The logistics role of physical stores in the e-commerce channel of an omni-channel retailer - Abreu, Helena Margarida de Sousa (2020)
This paper explores how physical stores may be integrated in the online operations of an omni-channel retailer. A literature review enabled the creation of an initial framework, which was then validated by expert interviews. It was found that savings in transportation costs may support store fulfillment, while service criteria favor the alternatives. Ultimately, the retailer’s operationalpositioning defines the most important considerations for this decision. Transportation savings also support the use of stores in the delivery of online orders, and the speed of reintegration of returned items into the firm’s inventory encourages the use of stores to process returns